2009
DOI: 10.1152/ajpregu.91055.2008
|View full text |Cite
|
Sign up to set email alerts
|

The spleen is required for 5-HT1Areceptor agonist-mediated increases in mean circulatory filling pressure during hemorrhagic shock in the rat

Abstract: The 5-HT(1A) receptor agonist, 8- OH-DPAT, increases whole body venous tone (mean circulatory filling pressure; MCFP), and attenuates metabolic acidosis in a rat model of unresuscitated hemorrhagic shock. To determine whether improved acid-base balance was associated with sympathetic activation and venous constriction, MCFP, sympathetic activity (SA), and blood gases were compared in hemorrhaged rats following administration of 5-HT(1A) receptor agonist 8-OH-DPAT, the arterial vasoconstrictor arginine vasopres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is clear that changes in RSNA often do not track with changes in sympathetic drive to other vascular beds that are important in maintaining peripheral resistance (26). Nevertheless, we have found that changes in RSNA parallel those of splanchnic nerve activity during progressive blood loss and subsequent hemorrhagic shock (43). Thus the uncoupling of blood pressure recovery from RSNA recovery was surprising.…”
Section: Discussionmentioning
confidence: 60%
“…It is clear that changes in RSNA often do not track with changes in sympathetic drive to other vascular beds that are important in maintaining peripheral resistance (26). Nevertheless, we have found that changes in RSNA parallel those of splanchnic nerve activity during progressive blood loss and subsequent hemorrhagic shock (43). Thus the uncoupling of blood pressure recovery from RSNA recovery was surprising.…”
Section: Discussionmentioning
confidence: 60%
“…Vasopressin also increases venous vascular tone so that mean systemic filling pressure is increased by vasopressin administration [41] . This effect should increase venous return.…”
Section: Vasopressin and Its Effects On Vascular Tonementioning
confidence: 99%
“…However, there was no longer any group difference in MCFP 20 min after the start of hemorrhage. This was surprising given our evidence that this hemorrhage model demonstrates a significant and persistent secondary increase in sympathetic activity that tends to peak 25 min after the start of hemorrhage (30). We expected that the progressive rise in sympathetic activity would increase venoconstriction in intact animals, but not SD rats.…”
Section: Splanchnic Control Of Mcfp and Venous Tonementioning
confidence: 90%
“…The 1/60 factor accounts for the difference in compliance between the arterial and venous vasculature in the rat. Measurements of VPP and FAP were taken once hemodynamic equilibrium was reached, usually, within 5 s of circulatory arrest, prior to activation of sympathetic reflexes (30). Total blood withdrawn was weighed to obtain a measure of total loss assuming a blood density of 1 g/ml.…”
Section: Experimental Protocolsmentioning
confidence: 99%